2016
DOI: 10.1002/ajmg.a.38031
|View full text |Cite
|
Sign up to set email alerts
|

Population screening for spinal muscular atrophy: A mixed methods study of the views of affected families

Abstract: Autosomal recessive conditions are a significant health burden with few treatments. Population carrier screening has been suggested as a means to tackle them. Little is known about the views of affected families despite the potential for direct impacts on them. Data are presented on attitudes among families affected by Spinal Muscular Atrophy (SMA) toward two population screening programs, pre‐conception, and prenatal. Data were gathered through qualitative interviews (n = 36) and a survey (n = 337). Eighty‐tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
62
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 39 publications
(72 citation statements)
references
References 38 publications
7
62
3
Order By: Relevance
“…We have previously shown that adults with Type II have a more positive view on the disease than adults with Type III (Boardman et al 2017; Table 4). Similar differences to those reported between Types II and III were also seen between adults with Type II and IV SMA (Table 4).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…We have previously shown that adults with Type II have a more positive view on the disease than adults with Type III (Boardman et al 2017; Table 4). Similar differences to those reported between Types II and III were also seen between adults with Type II and IV SMA (Table 4).…”
Section: Resultsmentioning
confidence: 93%
“…The data reported in this study are derived from a larger study of attitudes towards screening for SMA amongst both adults with SMA and their family members, the findings of which are reported elsewhere (Boardman et al 2017). While family members are an important stakeholder group in debates around genetic screening in their own right, people with genetic conditions have unique experiential knowledge of the condition in question and are set to affected by population genetic screening in very specific ways (Chen and Schiffman 2000; Allyse et al 2015).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study has revealed that families and adults affected by hemophilia are largely aware of the range of possible impacts for them should screening be introduced and these concerns were key to explaining why support for preconception and prenatal genetic screening were markedly lower among families and adults living with hemophilia than has been observed in relation to other genetic conditions, such as Spinal Muscular Atrophy (Boardman et al, ). Indeed, the transition of hemophilia from a condition that was fatal in childhood in the 1970s, to one that is largely treatable, is likely to have influenced families’ views on the necessity and value of screening for the disorder.…”
Section: Discussionmentioning
confidence: 98%
“…However, in spite of this scepticism around the reproductive value of screening for haemophilia, there was nevertheless support for the idea that NGS could be used by the parents of already affected children, to inform decisions about their future pregnancies. This finding is noteworthy as it suggests that the reproductive decisions and attitudes of already affected families are viewed differently by the haemophilia community than those made by the general population, highlighting the positive way that “experiential knowledge” and insight are valued in the appraisal of future affected lives . Indeed, the families and adults who participated in this survey had direct—and often extensive—knowledge of life with haemophilia, with 136/327 participants (42%) (Table ) of the sample having more than two people in their family living with haemophilia—a much higher rate of inter‐family recurrence than has been noted by studies of screening attitudes within families affected by other genetic conditions …”
Section: Discussionmentioning
confidence: 90%